XIAP protection of photoreceptors in animal models of retinitis pigmentosa. - Kevin C Leonard; Dino Petrin; Stuart G Coupland; Adam N Baker; Brian C Leonard; Eric C LaCasse; William W Hauswirth; Robert G Korneluk; Catherine Tsilfidis (PLoS ONE, 2007)
BACKGROUND: Retinitis pigmentosa (RP) is a blinding genetic disorder that is caused by the death of photoreceptors in the outer nuclear layer of the retina. To date, 39 different genetic loci have been associated with the disease, and 28 mutated genes have been identified. Despite the complexity of the underlying genetic basis for RP, the final common pathway is photoreceptor cell death via apoptosis. METHODOLOGY/PRINCIPAL FINDINGS: In this study, P23H and S334ter rhodopsin transgenic rat models of RP were used to test the neuroprotective effects of anti-apoptotic gene therapy. Adeno-associated viruses (AAV) carrying the X-linked inhibitor of apoptosis (XIAP) or green fluorescent protein (GFP) were delivered subretinally into the eye of transgenic rat pups. Histological and functional measures were used to assess neuroprotection. XIAP is known to block apoptosis by inhibiting the action of caspases-3, -7 and -9. The results show that XIAP gene therapy provides long-term neuroprotection of photoreceptors at both structural and functional levels. CONCLUSIONS/SIGNIFICANCE: Our gene therapy strategy targets the apoptotic cascade, which is the final common pathway in all forms of retinitis pigmentosa. This strategy holds great promise for the treatment of RP, as it allows for the broad protection of photoreceptors, regardless of the initial disease causing mutation.